Twisted holography - Kevin Costello; Davide Gaiotto (Journal of High Energy Physics)
Abstract We derive and test a novel holographic duality in the B-model topological string theory. The duality relates the B-model on certain Calabi-Yau three-folds to two-dimensional chiral algebras defined as gauged βγ systems. The duality conjecturally captures a topological sector of more familiar AdS5/CFT4 holographic dualities.